“Yellow Perils,” Revived: Exploring Racialized Asian/American Affect and Materiality Through Hate Discourse over the COVID-19 Pandemic - Keisuke Kimura (Gonzaga Library Publishing, 2021)
The goal of this essay is to explore what kind of hate is produced against Asian bodies in reaction to the COVID-19 pandemic. By centering Asian/American affect and materiality – marginalized voices, narratives, and feelings of Asian/Americans as affective-performative texts, this essay attends to critique the historical continuum of racial discrimination against Asian/Americans (i.e., yellow peril) and advocate for social justice, equality, and inclusion in the U.S. Overall, I argue that Asian/American bodies are both physiologically and ideologically desensitized, dehumanized, and weaponized as the revival of yellow perils over the COVID-19 pandemic. Moreover, this essay highlights the possibility of adding affective and performative lenses in Critical Intercultural Communication research, exploring the politics of Asian/American bodies and the hate discourse as a case study for further academic conversations in Asian/American scholarship in Communication.